2019
DOI: 10.1021/acsnano.9b04436
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Polydopamine Platforms: Synthesis and Promising Applications for Surface Modification and Advanced Nanomedicine

Abstract: As a mussel-inspired material, polydopamine (PDA), possesses many properties, such as a simple preparation process, good biocompatibility, strong adhesive property, easy functionalization, outstanding photothermal conversion efficiency, and strong quenching effect. PDA has attracted increasingly considerable attention because it provides a simple and versatile approach to functionalize material surfaces for obtaining a variety of multifunctional nanomaterials. In this review, recent significant research develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
473
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 797 publications
(475 citation statements)
references
References 195 publications
2
473
0
Order By: Relevance
“…In general, the synthesis of polymer capsules is rather complex, work-intensive, and therefore expensive [104]. PDA capsules, on the other hand, are comparatively easy to produce [105]. Moreover, the unique properties of PDA combined with drug loading and the simultaneous possibility of ligand grafting add to the benefit of creating capsules of the material.…”
Section: Pda Capsulesmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the synthesis of polymer capsules is rather complex, work-intensive, and therefore expensive [104]. PDA capsules, on the other hand, are comparatively easy to produce [105]. Moreover, the unique properties of PDA combined with drug loading and the simultaneous possibility of ligand grafting add to the benefit of creating capsules of the material.…”
Section: Pda Capsulesmentioning
confidence: 99%
“…Various modifications of this approach have been reported to date. For instance, CaCO 3 microparticles, silica NPs, MnCO 3 particles, and polystyrene spheres have recently been used as templates to produce PDA capsules of different shapes and sizes [105].…”
Section: Pda Capsulesmentioning
confidence: 99%
“…MPDA showed excellent biocompatible and signal enhancement as NPs‐based contrast agents, not only use as single imaging agent but also as a multimodel imaging platform. [ 29,61 ] MPDA that further loaded with active therapeutic ingredients has also been developed for imaging‐guided therapy. This section will give an overview of recent investigations that involve the design, synthesis, and performance of using MPDA for medical imaging and imaging‐guided therapies.…”
Section: Application Of Mpda In Theranosticsmentioning
confidence: 99%
“…[22][23][24] With these attractive properties, PDA and its derivatives have shown great potential in a wide range of applications across the biomedical, and materials sciences, as well as in the applied engineering and technology elds. [25][26][27][28][29][30][31] For example, Cai et al recently reported a new kind of PDA-based porous nanoparticles as a drug carrier for synergistic thermo-chemotherapy, therein a signicant promotion effect of near-infrared irradiation on the drug release was observed. 29 In the present work, we chose Sandalore as the model compound and designed a photothermo-responsive nanocarrier for the encapsulation and controlled release of low volatile fragrances.…”
Section: Introductionmentioning
confidence: 99%